2015
DOI: 10.1186/s12970-015-0100-0
|View full text |Cite
|
Sign up to set email alerts
|

A high protein diet (3.4 g/kg/d) combined with a heavy resistance training program improves body composition in healthy trained men and women – a follow-up investigation

Abstract: BackgroundThe consumption of a high protein diet (>4 g/kg/d) in trained men and women who did not alter their exercise program has been previously shown to have no significant effect on body composition. Thus, the purpose of this investigation was to determine if a high protein diet in conjunction with a periodized heavy resistance training program would affect indices of body composition, performance and health.MethodsForty-eight healthy resistance-trained men and women completed this study (mean ± SD; Normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 21 publications
7
115
1
6
Order By: Relevance
“…In brief, we found no deleterious effects of a high protein diet (2.51–3.32 g/kg/d) over a 1-year period. Prior work from our lab has shown that consuming a high protein diet in the short term has no harmful effects on any clinical measure (i.e., blood lipids and comprehensive metabolic panel) [6, 7]. …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In brief, we found no deleterious effects of a high protein diet (2.51–3.32 g/kg/d) over a 1-year period. Prior work from our lab has shown that consuming a high protein diet in the short term has no harmful effects on any clinical measure (i.e., blood lipids and comprehensive metabolic panel) [6, 7]. …”
Section: Discussionmentioning
confidence: 99%
“…Prior work from our laboratory has shown that consuming protein (2.3–3.4 g/kg/d) in amounts that are 3-4 times greater than the RDA results in a similar FFM increase for both the normal and high protein groups [6]; however, the high protein group lost more fat mass compared to the normal protein group in spite of the fact that they consumed on average ~400 kcals more per day over the treatment period. This is in contrast with the current study that showed no change in body composition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, lots of interventional nutritional studies have been conducted, and many meta-analyses and comprehensive reviews have assessed the effects of diet to the health [2][3][4][5][6][7]. Some investigators have suggested that trained person may have a lower requirement for protein due to increased efficiency of use of protein.…”
Section: Discussionmentioning
confidence: 99%